Therapeutic landscape of Fabry disease: advances and challenges from classical strategies to emerging therapies - Zhang, Miao; Wang, Chendan (Frontiers in Medicine, 2025)
Fabry disease (FD), as an X-linked lysosomal storage disorder (LSD), has seen significantly improved in patient prognosis since enzyme replacement therapy (ERT) was applied clinically in 2001. However, ERT has drawbacks such as immunogenicity, individual efficacy variability, and long-term treatment burdens. With deeper insights into the multidimensional pathological mechanisms of FD and breakthroughs in new delivery systems (such as mRNA therapy, engineered adeno-associated virus vectors), various emerging therapies have gradually developed. Nevertheless, each therapeutic strategy still faces areas needing improvement due to high disease heterogeneity, cytotoxicity, insufficient targeted tissue delivery efficiency, and a lack of long-term safety data. This article systematically reviews the development of different treatment strategies for FD, outlines the evolution from ERT clinical application to emerging technologies like novel vector delivery, analyzes the technical breakthroughs and clinical limitations of therapies at each stage, reveals the intrinsic connection between deepened understanding of pathological mechanisms and innovative treatments, and explores potential optimization directions for future treatment strategies based on global accessibility data.